The social determinants of health in Africa from a political economy perspective: an exploratory contribution - (:unkn) unknown (My University, 2020)
This article investigates the shortcomings in the implementation of an approach based on the social determinants of health in sub-Saharan Africa. This approach is extended by looking at health and development from a political economy perspective. This perspective acknowledges the non-linear nature of the political decision-making process and the absence of any institutional ideal type. The notion of institutional complementarities is used to investigate the deficiencies in this area in sub-Saharan Africa. It will be shown that the health programmes are based on a rationalist postulate and vertical concept of the problems. They are reflected in low levels of institutional complementarity. The article’s contribution to the literature rests on its use of an expanded political economy perspective to help bridge the gap between public health and analyses of public policy.
Keywords: African Research